Minuartio valentinae-Quercetum pyrenaicae: A new Iberian broad-leaved oak forests in the eastern coastal mountains and their seral plant communities. - Vilches de la Serna, Beatriz; Merle, Hugo; Ferriol, María; Sánchez-Mata, Daniel; Gavilán, Rosario G. (Lazaroa, 2013)
The study of Quercus pyrenaica forests in eastern areas of the Iberian Peninsula has differentiated a set of relevés from the Sierra de Espadán (Castellón). They are located in subhumid sites in the upper mesomediterranean to low supramediterranean belt, in the Valenciano-Tarraconense Mountains. A new forest Minuartio valentinae-Quercetum pyrenaicae is therefore described here, together with its main seral communities.